The relevance of the South African sectional titles law in interpretation and application of the sectional titles legislation of Botswana : an analysis of provisions pertaining to establishment of schemes - Serumula, Doreen Lame (Stellenbosch : University of Stellenbosch, 2011)
Thesis (LLM )-University of Stellenbosch, 2004.